O processo eletrônico na justiça do Brasil - Ruschel, Aírton José (2010)
The demands of the Brazilian judiciary have been increasing, like others democratic countries. The Conselho Nacional de Justiça (CNJ) has been stipulating goals for the tribunals to improve the quality of their services and accelerate the resolution of the processes. One of the initiatives of larger impact is the implantation of the Electronic Process which will totally eliminate the use of paper and will accelerate the resolution of the processes. For the citizen through the internet have access to the justice, the qualification and expansion of the broadband infrastructure is needed, and the increase of access points need to happen. Besides, the citizen has to pass in an inclusion process, not only in the new Information and Communication Technologies (ICT), but mainly to have an understanding of the juridical knowledge contained in his own judicial process.